REGULATION OF THE ACTIVITY OF MATRIX METALLOPROTEINASES AND THEIR ROLE IN THE BODY - Bazarova Nigina Sobirzhanovna (Web of Journals Publishing, 2024)
The development of inhibitors of zinc-containing metalloproteinases in most cases is aimed at MMP, inhibitors, since excessive concentrations of these proteinases in the body can lead to the development of certain groups of diseases. In this regard, the search for MMP inhibitors has gained great popularity. Inhibitors of other existing metalloprotenases, such as CPA, TLN, NEP, TACE, etc., are created for experimental purposes to study the molecular structure, as a result of which their number is limited. The lack of knowledge about the regulation of MMP activity at the posttranscriptional level, especially in vivo, is an important point that we should take into account in future studies.
Keywords: Inhibitor, metalloproteinases, zinc-containing, regulation, activity.